Staging the Other: Regarding the Negotiation between Spectatorship and Critical Citizenship in the Performance Third Generation - Byrdal Jørgensen, Tine (Nordic Theatre Studies, 2018)
Through an analysis of the performance of Third Generation, this article discusses the ethical claim activated in documentary theatre and has the encounter with the Other as its leitmotif. Third Generation puts a Gordian knot between Germany, Israel and Palestine into relief by bringing actors from these three countries – each with their own individual family history of violence – onto the stage. The article identifies the critical potential of the staging by exploring how the performance offers the audience two contrasting modes of perception. One of which is trying to create and maintain the illusion of authenticity that is produced by the biographical elements. The other challenges this illusion. In dialogue with Erika Fischer-Lichte’s The Transformative Power of Performance, the author points out how the interplay between the two modes of perception creates an increased awareness of the act of perceiving the Other. Via Derrida and Butler, this perceiving act is then set in relation to Lévinas’ ethical concept of the subject as a host(age) – the subject as held captive by the Other and as a hospitable host for the Other. Offering this ethical frame for the analysis, the article traces how and by which means documentary theatre rearticulates a complex ethical relation between the Other on Stage and the eye (I) of the spectator. In conclusion, this potential is discussed in relation to critical citizenship.